Teaching behaviour as a function of faculty's teaching philosophy - Carolin Kreber (Adult Education Research Conference, 1994)
The intent of this study was to investigate whether the implicit goals of higher education, critical thinking and self-direction in learning, are accounted for in the university setting by faculty who, on an espoused level, subscribe to these goals. Results indicate that some discrepancies existed between faculty's espoused philosophy of teaching and their observed teaching behaviour. Instructors' teaching behaviour, however, was a function of their personal theory of practice (theory-in-use). The repertory grid is suggested to be a suitable tool for identifying underlying assumptions. Psychological type and locus of control orientation are suggested to make a difference in the way faculty understand themselves as teachers; however, the small number of participants does not allow for any generalizations to be made.